Hybrid GI-DIC measurement procedure for hierarchical assessment of strain fields. (February 2019) - Malesa, Marcin; Kowalczyk, Piotr; Dymny, Grzegorz; Skrzypczak, Pawel; Salbut, Leszek; Pakula, Anna
Highlights: Hybrid DIC – grating interferometry measurement methodology has been presented. DIC-GI calibration procedure has been developed. The method has been used for laboratory measurements of a specimen with a blind hole. Improvement of the measurement results have been obtained. Abstract: Engineering design supported by numerical modeling allows to build devices optimized in terms of price, weight and parameters. Optimized designs includes complex components and new materials that in many cases have to be experimentally investigated. In the paper we present a hybrid measurement methodology, that combines the advantages of Grating Interferometry and Digital Image Correlation techniques and allows strain measurements with different accuracy levels at the same time. Both methods are used simultaneously in a single setup in order to reduce time and cost of the required experimental mechanics measurements and in consequence - speed up the design process of engineering objects.